SISTEM PEMERINTAHAN DESA DALAM TINJAUAN SEJARAH POLITIK DI INDONESIA - Amaliatulwalidain Amaliatulwalidain (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
The system of village governance in Indonesia has undergone various tidal history and political processes. The history and political process that colored the lowest system of government in Indonesia, has been started since the colonial period of Dutch colonization to the Japanese invaders, it is proven through the intervention of both Dutch colonial and Japanese in the governance system of village governance in the state and politics in Indonesia. During the Dutch administration period, the regulation of village governance was regulated in I.G.O. Stb. 1906-83 (Inlandsche Gemeente Ordonantie Java en Madoera) and I.G.O.B. Stb. 1938-490 yo.681 (Inlandsche Gemeente Ordonantie Buitengewesten). While the Japanese colonial period, the regulation of the village government system is regulated in Osamu Seirei regulation No.27 of 1942. Not stop there, after Indonesia's independence, especially during the Old Order government, the regulatory policy on village governance system was then reinforced by Law no. 19 of 1965 on Desa Praja in lieu of the policy of I.G.O, I.G.O.B and Osamu Seirei. And the last time when the New Order government came to power, the village government system experienced the most significant change with the enactment of Law No. 5 of 1979 on Village Government, where Law No. 5 of 1979 became a phenomenal law that lasted long enough period of reform.Keywords : Village Governance System, Political History of Indonesia